EOLOCY OF PASTORAL AREAS IN THE ARID ZONE OF RAjasthan - Gupta, R K (Annals of Arid Zone, 2016)
Area, landuse and Climate or pastoral areas of arid Rajasthan has been reviewed. Grasslands have been divided into I. Ephemeral drought evading, 2. Perennial drought evading 3. Perennial drought resistant and 4 Perennial. drought resisting semisucculent type. Distribution of the main grassland types with regard to climate and soil types is discussed. Inter-relation of grassland, animal population and stocking rate has been given. Suggestions for collecting data on consumers of the native vegetation and decomposers have been highlighted for a better understanding of the range ecosystem in the arid regions of Rajasthan.